2013
DOI: 10.1021/ac402889z
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemiluminescence Biosensor Based on Au-ITO Hybrid Bipolar Electrode Amplification System for Cell Surface Protein Detection

Abstract: Here we developed a novel hybrid bipolar electrode (BPE)-electrochemiluminescence (ECL) biosensor based on hybrid bipolar electrode (BPE) for the measurement of cancer cell surface protein using ferrocence (Fc) labeled aptamer as signal recognition and amplification probe. According to the electric neutrality of BPE, the cathode of U-shaped ITO BPE was electrochemically deposited by Au nanoparticles (NPs) to enhance its conductivity and surface area, decrease the overpotential of O2 reduction, which would corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 20 publications
0
81
0
Order By: Relevance
“…On the basis of this concept, bipolar electrochemistry has been used for materials preparation and fabrication, 55 sensing, 56 screening, 57 microswimmers. 58 Based upon the splitting of water, Kuhn and co-workers have designed and fabricated a lot of bipolar micromotors and channels.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this concept, bipolar electrochemistry has been used for materials preparation and fabrication, 55 sensing, 56 screening, 57 microswimmers. 58 Based upon the splitting of water, Kuhn and co-workers have designed and fabricated a lot of bipolar micromotors and channels.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, indium tin oxide (ITO) has recently been used as thin film electrodes in electrochemical biosensors [3] owing to its good electrical conductivity and high transparency to optical wavelengths, resulting in a good candidate for either electrochemical and/or optical biosensors. Few studies on the utilization of thin ITO films as biosensing electrodes can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Same authors reported later an improved system to determine the dynamic cellular attachment, spreading and proliferation of endothelial cells [5]. Indium tin oxide has been used recently in combination with gold for the development of an electrochemiluminescent biosensor for detecting cancer cell surface proteins [6].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is a powerful analytical technique due to its high sensitivity, wide linear range, low background and simple instrumentation [1][2][3][4][5][6]. One of the mostly used ECL systems is luminol-H 2 O 2 system because of its low oxidation potential, inexpensive reagent consumption and the high emission yields [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%